The PERAN ADVOKAT DALAM MENANGANI TINDAK PIDANA KEKERASAN SEKSUAL TERKAIT BUDAYA HUKUM DI TENGAH MASYARAKAT - Indra Mangiwa, Marthen; Ratnawati Gultom, Elfrida (UNES Law Review, 2022)
The purpose of this Paper is to discuss the function of advocates to educate the public regarding the passage of Laws Number 12 of 2022 concerning the Crime of Sexual Violence (“The Regulation”) which is expected to be a solution to the problem of sexual violence in Indonesia. How the role of advocates so that The Regulation can be well understood by the society, especially with regard to the application of the Articles contained in it? How the role of the Advocate so The Regulation doesn’t cause multiple interpretations in the society? Certainly, The Regulation needs the role of law enforcement, especially for advocates so that its application is effective and provides benefits, especially for the victims of sexual violence in the society and it requires the development of the ability of legal practitioners such as judges, prosecutors, police, advocates to have a sense of critical in applying the Rules. The research method used on writing this Paper is to use normative legal research methods, through a Juridical approach. The conclusion is that Law Number 12 of 2022 concerning the Crime of Sexual Violence can be a solution to the problem of sexual violence cases in Indonesia, however, the regulation requires the support of developing the ability of legal practitioners specifically advocates to have a sense of critical in applying it to become a rules whose application is effective and provides benefits, especially to the victims of sexual violence in the society.